Memahami Perilaku Kurangnya Aktivitas Olahraga pada Wanita Pekerja Kantoran dengan Pendekatan Teori Health Belief Model: Understanding the Behavior of Lack of Sport Activities in Female Office Workers with Health Belief Model Theory Approach - Luh Anggi Distya Pratiwi (Jurnal Surya Medika (JSM), 2023)
Lack of exercise caused less physial activities and influenced the lifestyle. In female office workers who do not exercise regularly, most of them have low perceived susceptibility, but they have faith and are aware of the impact of the disease or condition (perceived severity) and have low perceived benefits. The purpose of this research was to determine factors affecting the behavior of lack of sports in female office workers by using Health Belief Model theory approach. This research used qualitative approach with descriptive research design and cross sectional approach. The populations in this research were female office workers in Yogyakarta City. Samples in this research were based on suitability and adequacy. The samples needed in this research were limited to 28 people consist of female office workers aged 25-50 years. The research instrument used interview guide. Data collection in this research used one-on-one interview/personal interview method. Data analysis used content analysis method. The research results show that lack of sports activities are based on the perceived obstacles and self-confidence. Several obstacles that cause female office workers to do less exercise are obstacle from within (busy with work in the office), obstacle due to body laziness as well as uncertainty in allocating time.